## Trending News

# if h(x) = ln(2-3x)^5, find H (0)?

### 6 Answers

- 1 month ago
It is impossible to find H(0) from and expression given as h(x). The capital letter and small letter changes the whole thing. Unless if it was just a typo, then

H(0) or h(0) (whichever one is correct)

= ln[2-3(0)]^5 (just replace x with 0)

= ln2^5

= 5ln2 (law of logarithm puts 5 here)

≈ 5 × 0.693

= 3.465

- Login to reply the answers

- KrishnamurthyLv 71 month ago
h(x) = ln(2 - 3x)^5

h(0)

= ln(2)^5

= 0.160002698

- Login to reply the answers

- MyRankLv 61 month ago
h(x) = ln(2-3x)^5

h(0) = ?

h(x) = 5ln(2-3x)

put x = 0

h(0) = 5ln(2-3(0))

h(0) = 5ln(2)

Source(s): http://myrank.co.in/- Login to reply the answers

- husoskiLv 71 month ago
If that's the logarithm of the whole expression:

h(x) = ln [(2 - 3x)^5] = 5 ln (2 - 3x)

...then h(0) = 5 ln 2 ~~ 3.4657

If that's the logarithm raised to the 5th power:

h(x) = [ln (2 - 3x)] ^ 5 .... also written as log^5 (2 - 3x)

...then h(0) = (ln 2)^5 ~~ 0.16000

The second interpretation is the one most commonly used in typewritten expressions when using the function notation as in "ln(x): instead of using ln as an operator as in "ln x".

- Login to reply the answers

- How do you think about the answers? You can sign in to vote the answer.
- llafferLv 71 month ago
Presuming that is:

h(x) = ln[(2 - 3x)⁵]

Which would simplify to:

h(x) = 5 ln(2 - 3x)

Solve for h(0): substitute 0 for x and simplify:

h(0) = 5 ln(2 - 3 * 0)

h(0) = 5 ln(2 - 0)

h(0) = 5 ln(2)

or approximately:

h(0) = 5(0.693147)

h(0) = 3.465735

- Login to reply the answers